Interactive and Collaborative Online Teaching With Artificial Intelligent & Nearpod - Alfakihuddin, Muhammad Lukman Baihaqi; Tjhin, Santo; Islam, Sri Susilawati; Setiawan, Iwan; Prasetyo, Ilham; Liman, Surya Danusaputro (Journal of Community Services: Sustainability and Empowerment, 2023)
The Covid-19 virus pandemic presents new challenges for schoolteachers and students to complete online learning. Educators conduct distance learning so the challenge is the lack of control that can be exercised over students. Engaging in learning is essential to create enthusiasm and interest in learning during online learning. The development of digital technology such as artificial intelligence and Nearpod can be used to create interesting learning that can increase the spirit of learning. This community service was conducted to teachers at SDN Sampay 01 and 02, Cisarua, Jawa Barat. The results of this community service show that the knowledge of teachers of both SDN Sampay 01 and 02 regarding the use of Artificial Intelligence and Nearpod technology increased after the service was held. In addition, the majority of teachers are also more confident with the use of technology in their teaching.